Internalization of Religious Moderation Values in the Qur'an Hadith Textbooks at Madrasah Aliyah - Muslim, Buhori; Mardhiah, Ainal; Djuned, Muslim (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
One of the programs to overcome religious conflicts through educational institutions is to develop a curriculum by internalizing the values of religious moderation in textbooks on Al-Qur'an and Hadith subjects. This paper examines the internalization of the values of religious moderation contained in Al-Quran hadith textbooks through the learning process at Madrasah Aliyah Negeri 3 Banda Aceh City. It also explores the supporting and inhibiting factors in the implementation. A qualitative approach was conducted through interviews, document review, and observation. Research informants were the principal, teachers who taught Al-Quran Hadith subjects in classes X, XI, and XII, and students representing each class. The data analysis techniques were data reduction, display or presentation of data, and conclusion drawing. The results showed many values of religious moderation in the Al-Quran hadith textbooks. Still, there were no clear and firm explanations for understanding these moderation values because the explanations and interpretations of verses and hadiths presented in the textbooks still need additional, more comprehensive explanations regarding content and from the teacher's side. Teachers internalizing the values of religious moderation still focused on oral presentation (lecture method) even though in other conditions, there is also urgency in implementing these values in direct and indirect learning. The obstacle teachers face in internalizing the values of religious moderation in Al-Quran hadith subjects is the lack of clear and comprehensive knowledge and understanding of the content of religious moderation values and appropriate methods for transforming these values.